Diagnostic accuracy of a noninvasive hepatic ultrasound score for non-alcoholic fatty liver disease (NAFLD) in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Goulart, Alessandra Carvalho; Oliveira, Ilka Regina Souza de; Alencar, Airlane Pereira; Santos, Maira Solange Camara dos; Santos, Itamar Souza; Martines, Brenda Margatho Ramos; Meireles, Danilo Peron; Martines, João Augusto dos Santos; Misciagna, Giovanni; Benseñor, Isabela Martins; Lotufo, Paulo Andrade (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Noninvasive strategies for evaluating non-alcoholic fatty liver disease (NAFLD) have been investigated over the last few decades. Our aim was to evaluate the diagnostic ac-curacy of a new hepatic ultrasound score for NAFLD in the ELSA-Brasil study. DESIGN AND SETTINGS: Diagnostic accuracy study conducted in the ELSA center, in the hospital of a public university. METHODS: Among the 15,105 participants of the ELSA study who were evaluated for NAFLD, 195 in-dividuals were included in this sub-study. Hepatic ultrasound was performed (deep beam attenuation, hepatorenal index and anteroposterior diameter of the right hepatic lobe) and compared with the hepatic steatosis findings from 64-channel high-resolution computed tomography (CT). We also evaluated two clinical indices relating to NAFLD: the fatty liver index (FLI) and the hepatic steatosis index (HSI). RESULTS: Among the 195 participants, the NAFLD frequency was 34.4%. High body mass index, high waist circumference, diabetes and hypertriglyceridemia were associated with high hepatic attenuation and large anteroposterior diameter of the right hepatic lobe, but not with the hepatorenal index. The he-patic ultrasound score, based on hepatic attenuation and the anteroposterior diameter of the right hepatic lobe, presented the best performance for NAFLD screening at the cutoff point ≥ 1 point; sensitivity: 85.1%; specificity: 73.4%; accuracy: 79.3%; and area under the curve (AUC 0.85; 95% confidence interval, CI: 0.78-0.91)]. FLI and HSI presented lower performance (AUC 0.76; 95% CI: 0.69-0.83) than CT. CONCLUSION: The hepatic ultrasound score based on hepatic attenuation and the anteroposterior diam-eter of the right hepatic lobe has good reproducibility and accuracy for NAFLD screening.